Socialism versus capitalism - Pigou, A. C. (London, 1954)
THESE chapters were written to serve as a basis for lectures in the manner of those collected in my Economics in Practice. As it turned out, they did not break up into divisions of suitable length, and so in fact were never actually spoken. In tone and structure, however, they are lectures. That is to say, they make no pretence to constitute a learned work, and are addressed, not to experts, but to the general reader. This must be my excuse for ignoring the international aspects of socialism. It is not the business of an academic economist, nor is it within his competence, to stand advocate for or against any political programme. But it is his business, and it should be within his competence, to set out in an orderly way the dominant considerations, so far as they are economic, which are relevant to the argument.
Keywords: Socialism